Обліково-аналітичне забезпечення управління необоротними активами підприємства - Брухаль, Тетяна Павлівна; Brukhal, Tetyana Pavlivna (Ірпінь, 2023)
На основі узагальнення розглянуто опрацювання наукових рекомендацій та пропозицій стосовно вдосконалення методики обліку і аналізу необоротних активів на досліджуваному підприємстві. За результатами дослідження сформульовані пропозиції щодо удосконалення обліку необоротних активів підприємства.

Based on the generalization, the development of scientific recommendations and proposals regarding the improvement of the method of accounting and analysis of non-current assets at the researched enterprise was considered. Based on the results of the study, proposals were formulated to improve the accounting of non-current assets of the enterprise.
Accounting and analytical support for the management of non-current assets of the enterprise
Keywords: послуги; облік послуг; методика та організація обліку витрат автотранспортних підприємств; аудит послуг; services; accounting of services; method and organization of cost accounting of motor transport enterprises; audit of services